Pax7 pioneer factor action requires both paired and homeo DNA binding domains. Issue 13 (1st July 2021) - Pelletier, Audrey; Mayran, Alexandre; Gouhier, Arthur; Omichinski, James G; Balsalobre, Aurelio; Drouin, Jacques
Abstract: The pioneer transcription factor Pax7 contains two DNA binding domains (DBD), a paired and a homeo domain. Previous work on Pax7 and the related Pax3 showed that each DBD binds a cognate DNA sequence, thus defining two targets of binding and possibly modalities of action. Genomic targets of Pax7 pioneer action leading to chromatin opening are enriched for composite DNA target sites containing juxtaposed sites for both paired and homeo domains. The present work investigated the implication of the DBDs in pioneer action. We show that the composite sequence is a higher affinity binding site and that efficient binding to this site involves both DBDs of the same Pax7 molecule. This binding is not sensitive to cytosine methylation of the DNA sites consistent with pioneer action within nucleosomal heterochromatin. Introduction of single amino acid mutations in either paired or homeo domain that impair binding to cognate DNA sequences showed that both DBDs must be intact for pioneer action. In contrast, only the paired domain is required for low affinity binding of heterochromatin sites. Thus, Pax7 pioneer action on heterochromatin requires unique protein:DNA interactions that are more complex compared to its simpler DNA binding modalities at accessible enhancer target sites.